Quantifying the impact of 4 R nutrient stewardship and cover cropping on soil health across the U.S. Corn Belt - Cecilia Crespo; Moges Kidane Biru; Marcio R. Nunes; John L. Kovar; Lori J. Abendroth; Ikechukwu V. Agomoh; Sylvie M. Brouder; Derek Carney; Laura E. Christianson; Craig F. Drury; Alison J. Eagle; Bryan Emmett; et al. (Soil and Tillage Research, 2026)

From Andes to the dry diagonal: phylogenomics and trait evolution elucidate the radiation of cacti in South American drylands - Monique Romeiro-Brito; Flávia M. Lanna; Milena C. Telhe; Bryan C. Carstens; Luciano A. Digiampietri; Daniela C. Zappi; Nigel P. Taylor; Fernando F. Franco; Evandro M. Moraes (Molecular Phylogenetics and Evolution, 2026)

What determines trophic niche breadth? A global analysis of freshwater fishes using isospaces - Friedrich Wolfgang Keppeler; Tommaso Giarrizzo; Carmen G. Montaña; Alphonse Adite; Şenol Akın; Ronaldo Angelini; Caroline C. Arantes; Evanilde Benedito; Thethela Bokhutlo; Rana El-Sabaawi; Alexandre Garcia; Ivan Gonzalez-Bergonzoni; et al. (Reviews in Fish Biology and Fisheries, 2026)

Application of multi-criteria decision making for groundwater potential mapping in Manabí, Ecuador - Luis Román-Piedra; Joselyne Solórzano; Kevin Padilla-Cáceres; Fernando Morante-Carballo; F. J. Montalván; Bryan G. Valencia; Paúl Carrión-Mero (Hydrogeology Journal, 2026)

Plastitar and pyroplastics as emerging vectors of coastal pollution: Chemical identification from Panjang Island (Java Sea) and Palm Beach, Florida - Dwi Amanda Utami; Lars Reuning; Lorenz Schwark; Robert K. Nelson; Bryan D. James; Robert F. Swarthout; Diane Buhler; Eliete Zanardi-Lamardo; Christopher M. Reddy (Marine Pollution Bulletin, 2026)

Widespread reproductive deficits in Chesapeake Bay ospreys - Bryan D. Watts; Chance Hines; Mitchell A. Byrd; Reese F. Lukei; Barton J. Paxton; Laura Duval; Keriann E. Spiewak; Greg D. Kearns; Daniel D. Day; Barnett A. Rattner (Frontiers in Marine Science, 2026)
Introduction Ospreys ( Pandion haliaetus ) are well-known sentinels of aquatic ecosystem health and are indicators of both environmental contaminants and fish stocks. The Chesapeake Bay supports one of the largest osprey breeding populations in the world, but recent studies have documented declining reproductive performance and increasing food stress in some portions of the estuary. Methods We monitored osprey nests (N = 571) throughout the Chesapeake Bay during the 2024 breeding season and compared breeding metrics between high-salinity (>10 parts per thousand [ppt]) and low-salinity (<5 ppt) study areas. We also compared contemporary breeding performance within four high-salinity sites to historical data collected during the 1980s. Results Salinity was strongly associated with breeding performance and the likelihood that pairs achieved productivity levels required for population maintenance. All high-salinity study areas functioned as demographic sinks, whereas low-salinity areas functioned as demographic sources. Breeding metrics including the proportion of pairs breeding, clutch size, nesting failure, brood reduction, and nestling loss all suggested greater food stress within high-salinity areas. Temporal comparisons documented substantial declines in reproductive performance between the 1980s and 2024 within high-salinity study sites. High-salinity sites during the 1980s exhibited breeding performance comparable to low-salinity sites in 2024. Discussion Although several factors may influence osprey productivity within the Chesapeake Bay, we suggest that reduced availability of Atlantic menhaden ( Brevoortia tyrannus ) is a primary driver of poor reproductive performance within high-salinity waters.

Challenges in applying high energy water accommodated fractions in oil toxicity testing - Aaron D. Redman; Michel Boufadel; Bryan Hedgpeth; Tara Reddington; Daniel J. Letinski; Martin Connelly; Lin Zhao; Thomas F. Parkerton (Chemosphere, 2026)

Knowing with the river: Situated risks of riverine communities in the Peruvian Amazon - Heidi D. Mendoza; Jonathan J. Valenzuela; Elisa N. C. Armijos; Anne F. Van Loon; Melanie Rohse; Johanna K. L. Koehler; Bryan Joel Mariano; Bruno T. C. Gonzalo; Paulo F. S. Diaz; Cesar P. A. Vasquez; Carlos J. A. Souza; Elsa A. V. Izaguirre; et al. (Ambio, 2026)
Dominant approaches to drought and flood risk often marginalize the social and temporal dimensions of how communities experience environmental change. This study explores how three riverine communities in the Peruvian Amazon—Bajo Belén, Tamshiyacu, and El Chino—generate and act on knowledge of river dynamics to sustain livelihoods amid increasing hydrological variability. Using storytelling with 45 participants (2023–2024), and co-produced seasonal calendars, we identified risk windows or periods of heightened vulnerability when river levels misalign with local expectations. These windows provide a situated lens into how risks are interpreted and navigated through embodied, relational, and adaptive strategies. Our findings highlight the centrality of place-based knowledge and temporal attunement to sustainable adaptation, challenging technocratic risk frameworks. By reframing hydrological extremes as relational and embedded in local rhythms, the study calls for more inclusive governance that reflects the socio-cultural and ecological specificities of hydrological risks.

From agriculture back to tropical rainforest: When does ecological succession stabilize hot and dry extremes? - Felicity L. Newell; Edith Villa-Galaviz; Constance J. Tremlett; Sebastián Escobar; Adriana Argoti; Nicole Büttner; Julio Carvajal; María F. Checa; Katrin Krauth; Gustavo Pazmiño-Otamendi; Karen M. Pedersen; Bryan Tamayo; et al. (Agricultural and Forest Meteorology, 2026)

Pandemic SHV-106-producing Klebsiella pneumoniae ST231 isolated from Brazilian hedgehog (Coendou spinosus) reveals an emerging environmental circulation of a high-risk multidrug-resistant lineage - Jacqueline Meyer; Jéssica A. Martins; Amanda Haisi; João P. Araújo Júnior; Gustavo H. Z. Winter; Raquel F. S. Raimondo; Marcelo M. Alievi; Marcos Bryan Heinemann; Natália C. Gaeta (Antonie van Leeuwenhoek, 2026)
Antimicrobial resistance (AMR) poses a major global health challenge, and wildlife has increasingly been recognized as an important sentinel for monitoring the environmental circulation of clinically relevant resistant bacteria. In this study, we report the phenotypic, genomic, and phylogenomic characterization of a multidrug-resistant (MDR) Klebsiella pneumoniae isolate recovered from a free-ranging wild porcupine ( Coendou spinosus ) in southern Brazil. An extended-spectrum β-lactamase (ESBL)-producing strain, designated UFRGS-ourico-23, was isolated during routine surveillance at a Wild Animals Care Unity. It exhibited resistance to β-lactams, quinolones, aminoglycosides, sulfonamides, and tetracycline. Whole-genome sequencing revealed a complex resistome, including bla SHV-106 , oqxAB , qnrB1 , aminoglycoside-modifying enzymes, sulfonamide, tetracycline, fosfomycin, and trimethoprim resistance genes, consistent with the MDR phenotype. Notably, ESBL production was mediated by the rare bla SHV-106 gene chromosomally located near the lactose operon. In addition, the UFRGS-ourico-23 strain belonged to the pandemic high-risk sequence type ST231. This is the first report of a bla SHV-106 in an animal-derived K. pneumoniae ST231 in Brazil. The strain also harbored a class 1 integron and conjugative IncFIB and Col440I plasmids carrying multiple resistance genes, as well as heavy-metal tolerance operons, suggesting co-selection pressures in anthropized environments. The phylogenomic analysis demonstrated close clustering with globally distributed, predominantly human-derived ST231 genomes, indicating limited core-genome divergence. Collectively, these findings document the emergence of a high-risk MDR K. pneumoniae ST231 clone in Brazilian wildlife and highlight the role of wild animals as reservoirs and sentinels of clinically relevant AMR lineages, reinforcing the need for integrated One Health genomic surveillance at the human–animal–environment interface.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Phytoremediation of an acid tar pit at Cinderhill, Derbyshire, UK: Lessons learned and future challenges - Matthew F. Johnson; Harvey Wood; Samantha Bryan; Sean Craig; Will Meredith; Colin Snape; Clement N. Uguna (Journal of Environmental Management, 2026)

Global analysis of nitrogen dioxide and formaldehyde column densities from the Pandora global network: Variability and implications for satellite validation - Jong-Uk Park; Subin Lim; Thomas F. Hanisco; Nader Abuhassan; Bryan K. Place; Apoorva Pandey; Alexander Cede; Martin Tiefengraber; Manuel Gebetsberger; Jinsoo Park; Jinsoo Choi; James H. Crawford; et al. (Remote Sensing of Environment, 2026)

An investigation of an outbreak of Salmonella Typhimurium infections linked to alfalfa sprouts – United States, 2022 - Mardea Caulcrick-Grimes; Brianna K.D. Loeck; Patricia Homola; Tong-Jen Fu; Jonathan Burgos; Daniela Schoelen; Robert Literman; Evelyn Ladines; Annemarie Buchholz; Grace Tung; Natalie Smith; Bryan F. Buss; et al. (Food Control, 2026)

Alternating self-administration sessions of cocaine and heroin impact drug-related motivation and vocalisations in rats - Kristian Adamatzky; Angharad C. Collins; Aldo Badiani; Bryan F. Singer (Psychopharmacology, 2025)
Rationale Animal models of addiction often study changes in motivation after repeated self-administration of a single drug. However, human users frequently consume multiple drugs, potentially altering their motivation and affective response. Objectives This study investigated how individual rats differentially self-administer cocaine and heroin, and whether motivation to take each drug was associated with affective states, as indicated by ultrasonic vocalisations (USVs). We also determined whether opioid antagonism (via naltrexone), which is known to decrease heroin-taking and associated USVs, also altered motivation and vocalisations for cocaine. Methods Male Lister Hooded rats, with surgically implanted catheters, self-administered cocaine and heroin on alternating days. Motivation was evaluated via drug intake escalation (fixed-ratio schedule), behavioural adaptation to dose reductions (behavioural economics), and progressive ratio breakpoints (with or without naltrexone). USVs were recorded and analysed using machine learning software (DeepSqueak). Results Rats escalated intake of both drugs during training. At the start of each session, rats rapidly self-administered cocaine or heroin; this drug-loading behaviour was associated with an increase in 50 kHz vocalisations. Rats altered their cocaine and heroin intake when drug doses decreased, and this was accompanied by reduced 50 kHz USVs. Lastly, naltrexone reduced progressive ratio breakpoints for heroin but not cocaine; naltrexone also decreased 50 kHz USVs for heroin (an effect which persisted). Conclusions Distinct patterns emerged in motivation and USVs between cocaine and heroin self-administration. Notably, USV frequency did not consistently align with motivation, especially when drug dosage changed. Future research may clarify this divergence.

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Applying the IUCN Global Ecosystem Typology to classify, describe, and map ecosystems based on regional data and Indigenous knowledge - Alys R. Young; Hugh F. Davies; Margaret L. Ayre; Alana Brekelmans; Brett A. Bryan; Jane Elith; Kate Hadden; Mavis Kerinaiua; David A. Keith; Donna L. Lewis; Kinjia M. Munkara‐Murray; Sarah Ryan; et al. (Conservation Biology, 2025)
Effective ecosystem conservation for biodiversity and human well‐being relies on accurate information. Consistent approaches to classifying, describing, and assessing ecosystems can improve understanding of ecological processes, threats, and management. We explored how the International Union for Conservation of Nature (IUCN) Global Ecosystem Typology—a global classification framework based on ecosystem function—could support the development of a classification of ecosystems for the Tiwi Islands, Australia, by incorporating scientific information and Indigenous Tiwi knowledge to facilitate environmental management and conservation. We synthesized ecosystem information from previous research, field data, reports, and Tiwi knowledge authorities to develop a classification, descriptions, and a map of 14 terrestrial ecosystem types. These ecosystem types were defined and described based on ecological processes and were broader yet largely congruent with existing vegetation classifications. Including functional properties accounted for variation in the vegetation physiognomy exhibited by dynamic and disturbance‐prone ecosystems, such as savannas. Because we considered Tiwi knowledge authorities and the IUCN Global Ecosystem Typology, our inventory included ecosystem types that were typically omitted from previous classifications, which should allow for more comprehensive assessments and management. Relating the new ecosystem typology to the IUCN Global Ecosystem Typology will facilitate comparisons among similar ecosystems, regarding, for example, effective threat abatement options. Describing the biota and processes opens new avenues for monitoring. More collaborative work is needed to explore how Western scientific ecosystem inventories operate alongside and in connection with management of Tiwi murrakupuni enacted by Tiwi people. Given the ongoing loss of biodiversity, ecosystem management must draw on information across domains, scales, and knowledge systems. We demonstrated an approach to this task and provided socioecologically relevant ecosystem information.

Rapid Global Deforestation Leaves Forest‐Dependent Raptors With Half of Their Suitable Habitat Remaining - Christopher J. O'Bryan; Zunyi Xie; Hongli Li; Evan R. Buechley; Martin K.‐F. Bader; James R. Allan; Ralph Buij (Global Change Biology, 2025)
Raptors—a group that includes hawks, eagles, owls, and vultures—are among the most imperiled vertebrates, with over half of species declining and one‐fifth threatened with extinction. Most raptors depend on forests for survival, yet the extent and consequences of recent deforestation within their ranges remain poorly understood. We analyzed high‐resolution global data on forest change between 2001 and 2023 within the ranges of 369 forest‐dependent raptor species. On average, these species have lost 10% of forest within their ranges since 2001. Seventy‐seven species had already lost at least 15% of additional forest cover within their ranges in the latter half of the 20th century. Currently, only 52% of forest cover remains within forest‐dependent species' ranges on average, with many forest specialists retaining less than 25% cover. Forest‐dependent raptors listed as Critically Endangered by the IUCN have lost the most forest and now retain the least forest cover within their ranges. Shifting agriculture is the primary driver of forest loss—particularly in tropical Africa and South America—followed by commodity‐driven deforestation in Southeast Asia. Because forest loss is frequently used as a proxy for extinction risk for raptors, our findings have direct applications for species threat assessments, regional conservation priorities, and global biodiversity commitments.

Individual variability in the nuclei of the human superior olivary complex - Yahya Farid; Bryan Lukyanenko; Sandra F. Witelson; Joan S. Baizer (Brain Structure and Function, 2025)
The superior olivary complex (SOC) receives auditory information from the cochlear nuclei. In nonhuman mammals, the SOC contains three nuclei: the lateral and medial superior olives (LSO, MSO) and the medial nucleus of the trapezoid body (MNTB). There are also periolivary neurons that are assigned to different nuclei in different mammals. The configuration of the SOC in the human differs from that in other species. The LSO is less well-defined; some authors do, and others do not, find an MNTB, and different authors recognize different periolivary nuclei. We have studied the organization of the human SOC using Nissl and immunostained sections of 12 brains from the Witelson Normal Brain Collection. We found an MSO in all cases although it varied in rostro-caudal extent. We did not consistently see a grouping of neurons consistent with an LSO in Nissl sections. Calbindin (CB) is expressed in neurons of the MNTB in several species. We found CB-immunoreactive (ir) cells in all human cases, some in the expected location of the MNTB, however these CB-ir neurons varied in number and location among cases. The variability in SOC configuration suggests there may also be individual variability in sound localization, a major function mediated by the SOC.

The impact of weather variation on the body condition of cape cobras (Naja nivea) in the Kalahari — implications for climate change - Kim J. Scholtz; Graham J. Alexander; Thilo F. Beck; Robin A. Maritz; Bryan Maritz (Journal of Arid Environments, 2025)

Is this spicy? Investigation of factors that influence spicy food choices by US older adults - Patrycja Urszula Żukowska; Bryan Michael L. Pepito; Helena Maria Andre Bolini; Carolyn F. Ross (Food Quality and Preference, 2025)

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Cobalt-60, Barium-133, Cesium-137, and Europium-152 migration from cementitious sources through sediment under field conditions - Reid F. Williams; Daniel I. Kaplan; Bryan J. Erdmann; Timothy A. DeVol; Brian A. Powell (Journal of Environmental Radioactivity, 2024)

Rethinking the association between green space and crime using spatial quantile regression modelling: Do vegetation type, crime type, and crime rates matter? - Ruoyu Wang; Claire L. Cleland; Ruth Weir; Sally McManus; Agustina Martire; George Grekousis; Dominic Bryan; Ruth F. Hunter (Urban Forestry & Urban Greening, 2024)

Edible insects: Understanding benzo(a)pyrene toxicokinetics in yellow mealworms for safe and sustainable consumption - Diogo N. Cardoso; Regina M.B.O. Duarte; Ana Rita R. Silva; Marija Prodana; Ana Góis; Patricia V. Silva; Amid Mostafaie; José Pinto; Pedro F. Brandão; Ivã G. Lopes; Bryan W. Brooks; Susana Loureiro (Science of The Total Environment, 2024)

Predictors of Adherence and Reasons for Non-adherence to Early Time-restricted Eating - F. Steger; C. Hanick; D. Bryan; S. Salvy; C. Peterson (Journal of the Academy of Nutrition and Dietetics, 2024)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Taking the sting out of scorpions: Electrophysiological investigation of the relative efficacy of three antivenoms against medically significant Centruroides species - Sam I.D. Campbell; Chun Yuen Chow; Edgar Neri-Castro; Alejandro Alagón; Aarón Gómez; Raúl Soria; Glenn F. King; Bryan G. Fry (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Development of a consistent geochemical model of the Mg(OH)2–MgCl2–H2O system from 25°C to 120°C - Andrew W. Knight; Charles R. Bryan; Carlos F. Jové-Colón (Applied Geochemistry, 2024)

Red-on-Yellow Queen: Bio-Layer Interferometry Reveals Functional Diversity Within Micrurus Venoms and Toxin Resistance in Prey Species - Daniel Dashevsky; Richard J. Harris; Christina N. Zdenek; Melisa Benard-Valle; Alejandro Alagón; José A. Portes-Junior; Anita M. Tanaka-Azevedo; Kathleen F. Grego; Sávio S. Sant’Anna; Nathaniel Frank; Bryan G. Fry (Journal of Molecular Evolution, 2024)
Snakes in the family Elapidae largely produce venoms rich in three-finger toxins (3FTx) that bind to the $$\upalpha _1$$ α 1 subunit of nicotinic acetylcholine receptors (nAChRs), impeding ion channel activity. These neurotoxins immobilize the prey by disrupting muscle contraction. Coral snakes of the genus Micrurus are specialist predators who produce many 3FTx, making them an interesting system for examining the coevolution of these toxins and their targets in prey animals. We used a bio-layer interferometry technique to measure the binding interaction between 15 Micrurus venoms and 12 taxon-specific mimotopes designed to resemble the orthosteric binding region of the muscular nAChR subunit. We found that Micrurus venoms vary greatly in their potency on this assay and that this variation follows phylogenetic patterns rather than previously reported patterns of venom composition. The long-tailed Micrurus tend to have greater binding to nAChR orthosteric sites than their short-tailed relatives and we conclude this is the likely ancestral state. The repeated loss of this activity may be due to the evolution of 3FTx that bind to other regions of the nAChR. We also observed variations in the potency of the venoms depending on the taxon of the target mimotope. Rather than a pattern of prey-specificity, we found that mimotopes modeled after snake nAChRs are less susceptible to Micrurus venoms and that this resistance is partly due to a characteristic tryptophan $$→$$ → serine mutation within the orthosteric site in all snake mimotopes. This resistance may be part of a Red Queen arms race between coral snakes and their prey.

Adapting the Marine Stewardship Council risk-based framework to estimate impacts on seabirds, marine mammals, marine turtles and sea snakes - Stephanie D. Good; Kate Dewar; Polly Burns; Keith Sainsbury; Richard A. Phillips; Bryan P. Wallace; Caterina Fortuna; Vinay Udyawer; Bruce Robson; Edward F. Melvin; Rohan J.C. Currey (Marine Policy, 2024)

Coyotes in the Great Basin desert do not exhibit a spatial response following the removal of anthropogenic water sources - Nadine A. Pershyn; Eric M. Gese; Erica F. Stuber; Bryan M. Kluever (Journal of Arid Environments, 2024)

Unconfined fishway design, implementation, and assessment for the emerald Shiner (Notropis atherinoides) in the Upper Niagara River, New York - Jundong Qiao; Sean J. Bennett; Joseph F. Atkinson; Paul A. Cocca; Sarah K. Delavan; Andrew R. Hannes; Bryan A. Hinterberger; Timothy J. Pede; Alicia Pérez-Fuentetaja; Richard J. Ruby (Ecological Engineering, 2024)

Mycotoxin contamination in the Arab world: Highlighting the main knowledge gaps and the current legislation - Mohamed F. Abdallah; Muhammad Gado; Doha Abdelsadek; Fatma Zahran; Nada Nabil El-Salhey; Ohaila Mehrez; Sara Abdel-Hay; Sahar M. Mohamed; Karl De Ruyck; Shupeng Yang; Gerard Bryan Gonzales; Elisabeth Varga (Mycotoxin Research, 2024)

Microbes, the ‘silent third partners’ of bee–angiosperm mutualisms - Shawn A. Steffan; Prarthana S. Dharampal; Jordan G. Kueneman; Alexander Keller; Magda P. Argueta-Guzmán; Quinn S. McFrederick; Stephen L. Buchmann; Rachel L. Vannette; Anna F. Edlund; Celeste C. Mezera; Nolan Amon; Bryan N. Danforth (Trends in Ecology & Evolution, 2024)

Update of the Cancer Potency Database (CPDB) to enable derivations of Thresholds of Toxicological Concern (TTC) for cancer potency - Chihae Yang; James F. Rathman; J. Vinicius Ribeiro; Monika Batke; Sylvia E. Escher; James W. Firman; Bryan Hobocienski; Rupert Kellner; Aleksandra Mostrag; Katarzyna R. Przybylak; Mark T.D. Cronin (Food and Chemical Toxicology, 2023)

Evaluation of an in vitro experimental platform of human polarized intestinal epithelial monolayers for the hazard assessment of insecticidal proteins - Cindi S. Zimmermann; Ryan F. Snow; Brittany Wilson-Mifsud; Kristine LeRoy; Chad Boeckman; Emily Huang; Carey A. Mathesius; Jason M. Roper; Bryan P. Hurley (Food and Chemical Toxicology, 2023)

Urbanization influences spatiotemporal patterns of roost site selection by black vultures and turkey vultures - Jacob E. Hill; Kenneth F. Kellner; Amanda E. Holland; Bryan M. Kluever; Morgan B. Pfeiffer; Travis L. DeVault; Jerrold L. Belant (Urban Ecosystems, 2023)
Roost locations can be an important contributor to vulture conflicts with humans, but factors influencing roost-site selection at a landscape level remain largely unexplored. Further, there has been little research comparing how these factors vary between nocturnal and diurnal roosting sites. We used remote cameras to document daily variation in vulture use of 21 roosts (20 communication/water towers and 1 natural roost) near Beaufort, South Carolina, USA from October 2019–August 2020. Numbers of vultures on roosts increased with decreasing urban cover and with greater distance to water, but were not influenced by habitat fragmentation or elevation. Roosts surrounded by greater proportions of urban cover were used more often during the day, whereas roosts adjacent to less urban cover were more commonly used at night. We suggest that this relationship results from a greater daytime association with human development, areas that likely provide food and favorable soaring conditions for vultures. Vultures tended to depart nocturnal roosts before sunrise and return within two hours of sunset, indicating that aircraft collision risk resulting from movement around nocturnal roosts would be elevated during these times. Several communication towers routinely had > 100 vultures roosting on them at once, likely contributing to conflict with humans. Our findings reiterate the generalism of these species and their capacity to exploit novel structures for roosting, which has likely contributed to range expansions and resultant increases in human-vulture conflicts over the past several decades.

Relationship between coliphage and Enterococcus at southern California beaches and implications for beach water quality management - Amity G. Zimmer-Faust; John F. Griffith; Joshua A. Steele; Bryan Santos; Yiping Cao; Laralyn Asato; Tania Chiem; Samuel Choi; Arturo Diaz; Joe Guzman; David Laak; Michele Padilla; et al. (Water Research, 2023)

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Controls on the frequency content of near-source infrasound at open-vent volcanoes: a case study from Volcán Villarrica, Chile - Bryan B. Rosenblatt; Jeffrey B. Johnson; Jacob F. Anderson; Keehoon Kim; Scott J. Gauvain (Bulletin of Volcanology, 2022)

Non-random fishery data can validate research survey observations of Pacific cod (Gadus macrocephalus) size in the Bering Sea - Kimberly M. Rand; Susanne F. McDermott; David. R. Bryan; Julie K. Nielsen; Ingrid B. Spies; Steven J. Barbeaux; Todd Loomis; John Gauvin (Polar Biology, 2022)

Global patterns of illegal marine turtle exploitation - Jesse F. Senko; Kayla M. Burgher; Maria del Mar Mancha‐Cisneros; Brendan J. Godley; Irene Kinan‐Kelly; Trevor Fox; Frances Humber; Volker Koch; Andrew T. Smith; Bryan P. Wallace (Global Change Biology, 2022)
Human exploitation of wildlife for food, medicine, curios, aphrodisiacs, and spiritual artifacts represents a mounting 21st‐century conservation challenge. Here, we provide the first global assessment of illegal marine turtle exploitation across multiple spatial scales (i.e., Regional Management Units [RMUs] and countries) by collating data from peer‐reviewed studies, grey literature, archived media reports, and online questionnaires of in‐country experts spanning the past three decades. Based on available information, we estimate that over 1.1 million marine turtles were exploited between 1990 and 2020 against existing laws prohibiting their use in 65 countries or territories and in 44 of the world's 58 marine turtle RMUs, with over 44,000 turtles exploited annually over the past decade. Exploitation across the 30‐year period primarily consisted of green (56%) and hawksbill (39%) turtles when identified by species, with hawksbills (67%) and greens (81%) comprising the majority of turtles exploited in the 1990s and 2000s, respectively, and both species accounting for similar levels of exploitation in the 2010s. Although there were no clear overarching trends in the magnitude or spatial patterns of exploitation across the three decades, there was a 28% decrease in reported exploitation from the 2000s to the 2010s. The 10 RMUs with the highest exploitation in the 2010s included seven green and three hawksbill turtle RMUs, with most reported exploitation occurring in RMUs that typically exhibit a low risk of population decline or loss of genetic diversity. Over the past decade, the number of RMUs with “moderate” or “high” exploitation impact scores decreased. Our assessment suggests that illegal exploitation appears to have declined over the past decade and, with some exceptions, is primarily occurring in large, stable, and genetically diverse marine turtle populations.

Rapid quantification of cannabinoids in beef tissues and bodily fluids using direct-delivery electrospray ionization mass spectrometry - Shubhashis Chakrabarty; Eric M. Serum; Thomas M. Winders; Bryan Neville; Michael D. Kleinhenz; Geraldine Magnin; Johann F. Coetzee; Carl R. Dahlen; Kendall C. Swanson; David J. Smith (Food Additives & Contaminants: Part A, 2022)

Extending null scenarios with Faddy distributions in a probabilistic randomization protocol for presence-absence data - Jorge A. Navarro Alberto; Bryan F. J. Manly; Ken Gerow (Environmental and Ecological Statistics, 2022)

The advantages and limitations of biophysical modelling as a tool for informing limit setting in New Zealand's barrier‐enclosed estuaries - Karin R. Bryan; Benjamin T. Stewart; Alex M. Port; Hannah F. E. Jones; Conrad A. Pilditch (New Zealand Journal of Marine and Freshwater Research, 2022)
Estuaries are the receiving environment for catchment‐derived contaminants, the fate of which depends on the interplay between the estuarine geomorphology and hydrodynamics. In large estuaries, biophysical processes are spatially and temporally‐diverse, which makes understanding and managing the impact of human activities challenging. Here we use two common modelling approaches to explore the advantages and limitations of biophysical modelling as a tool for limit setting in a large barrier‐enclosed estuary in New Zealand. The model shows the large spatial variation in water quality associated with low upper harbour flushing. Variations can also be attributed to spatial variation in processes (such as denitrification). Although the non‐linear interactions between processes within these models can limit the value of using specific detail of outputs for decision making, the general patterns and sensitivities can be used to define areas, explore connectivity, and provide some information when monitoring data is lacking. Even in a deterministic modelling environment, it can very difficult to attribute water quality variations output at one location to the loading that caused these variations. While biophysical modelling will likely remain a core tool for informing management, any future development of limit setting methods for estuaries should recognise the inherent constraints we describe here.

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Genomic evidence of an ancient inland temperate rainforest in the Pacific Northwest of North America - Megan Ruffley; Megan L. Smith; Anahí Espíndola; Daniel F. Turck; Niels Mitchell; Bryan Carstens; Jack Sullivan; David C. Tank (Molecular Ecology, 2022)
The disjunct temperate rainforests of the Pacific Northwest of North America (PNW) are characterized by late‐successional dominant tree species Thuja plicata (western redcedar) and Tsuga heterophylla (western hemlock). The demographic histories of these species, along with the PNW rainforest ecosystem in its entirety, have been heavily impacted by geological and climatic changes the PNW has experienced over the last 5 million years, including mountain orogeny and repeated Pleistocene glaciations. These environmental events have ultimately shaped the history of these species, with inland populations potentially being extirpated during the Pleistocene glaciations. Here, we collect genomic data for both species across their ranges to test multiple demographic models, each reflecting a different phylogeographical hypothesis on how the ecosystem‐dominating species may have responded to dramatic climatic change. Our results indicate that inland and coastal populations in both species diverged ~2.5 million years ago in the early Pleistocene and experienced decreases in population size during glacial cycles, with subsequent population expansion. Importantly, we found evidence for gene flow between coastal and inland populations during the mid‐Holocene. It is likely that intermittent migration in these species during this time has prevented allopatric speciation via genetic drift alone. In conclusion, our results from combining genomic data and demographic inference procedures establish that populations of the ecosystem dominants Thuja plicata and Tsuga heterophylla persisted in refugia located in both the coastal and inland regions of the PNW throughout the Pleistocene, with populations expanding and contracting in response to glacial cycles with occasional gene flow.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

C(3)1-TAg in C57BL/6 J background as a model to study mammary tumor development - Isadora F. G. Sena; Beatriz G. S. Rocha; Caroline C. Picoli; Gabryella S. P. Santos; Alinne C. Costa; Bryan O. P. Gonçalves; Ana Paula V. Garcia; Maryam Soltani-asl; Leda M. C. Coimbra-Campos; Walison N. Silva; Pedro A. C. Costa; Mauro C. X. Pinto; et al. (Histochemistry and Cell Biology, 2021)

Future carbon emissions from global mangrove forest loss - Maria F. Adame; Rod M. Connolly; Mischa P. Turschwell; Catherine E. Lovelock; Temilola Fatoyinbo; David Lagomasino; Liza A. Goldberg; Jordan Holdorf; Daniel A. Friess; Sigit D. Sasmito; Jonathan Sanderman; Michael Sievers; et al. (Global Change Biology, 2021)
Mangroves have among the highest carbon densities of any tropical forest. These ‘blue carbon’ ecosystems can store large amounts of carbon for long periods, and their protection reduces greenhouse gas emissions and supports climate change mitigation. Incorporating mangroves into Nationally Determined Contributions to the Paris Agreement and their valuation on carbon markets requires predicting how the management of different land‐uses can prevent future greenhouse gas emissions and increase CO 2 sequestration. We integrated comprehensive global datasets for carbon stocks, mangrove distribution, deforestation rates, and land‐use change drivers into a predictive model of mangrove carbon emissions. We project emissions and foregone soil carbon sequestration potential under ‘business as usual’ rates of mangrove loss. Emissions from mangrove loss could reach 2391 Tg CO 2 eq by the end of the century, or 3392 Tg CO 2 eq when considering foregone soil carbon sequestration. The highest emissions were predicted in southeast and south Asia (West Coral Triangle, Sunda Shelf, and the Bay of Bengal) due to conversion to aquaculture or agriculture, followed by the Caribbean (Tropical Northwest Atlantic) due to clearing and erosion, and the Andaman coast (West Myanmar) and north Brazil due to erosion. Together, these six regions accounted for 90% of the total potential CO 2 eq future emissions. Mangrove loss has been slowing, and global emissions could be more than halved if reduced loss rates remain in the future. Notably, the location of global emission hotspots was consistent with every dataset used to calculate deforestation rates or with alternative assumptions about carbon storage and emissions. Our results indicate the regions in need of policy actions to address emissions arising from mangrove loss and the drivers that could be managed to prevent them.

Genomic data from the Brazilian sibilator frog reveal contrasting pleistocene dynamics and regionalism in two South American dry biomes - Maria Tereza C. Thomé; Bryan C. Carstens; Miguel T. Rodrigues; João Alexandrino; Célio F. B. Haddad (Journal of Biogeography, 2021)
Aim Knowledge about the Neotropical dry formations, particularly the Caatinga, remains rudimentary compared to other biotas in the region. Here we address several biogeographical hypotheses by combining intense geographical and genomic sampling obtained for the Brazilian sibilator frog. We specifically test predictions related to the putative roles of past climate shifts (Pleistocene and Holocene) and local geographical barriers (past and current courses of the São Francisco River, SFR) in causing population differentiation in this species. Location Caatinga and eastern Cerrado. Taxon Brazilian sibilator frog Leptodactylus troglodytes . Methods We sequenced up to ~15,000 single nucleotide polymorphisms for 159 samples from 61 locations. We inferred genetic structure using spatial clustering and examined population sizes through time. We estimated the relationship among populations using phylogenetic reconstruction, estimated historical distributions with ecological niche modelling and inferred demographic history under isolation‐with‐migration models. Results Genetic diversity in L. troglodytes corresponds to biome boundaries, with one population in the Cerrado and two populations in the Caatinga, separated by the SFR. Demographic model selection indicates the Caatinga populations expanded since the end of the Pleistocene while the Cerrado population declined. Within the Caatinga, population expansion began earlier and was more extreme in the north. A continuous stability area maintained the two Caatinga populations, which share a common origin and began diverging in the mid‐Pleistocene, first with symmetric gene flow and later under pronounced migration from the north. Main conclusions We could not reject a role of past climate change in causing diversification of relictual populations in the Cerrado, but we found no evidence of multiple refuges or long‐term isolation within the Caatinga. Instead, diversification in this biome appears to be caused by the SFR acting as a ‘soft barrier’ that constrains migration over an extended period of time.

Prevalence of Acute Hypersensitivity Reactions in Pediatric Patients Receiving Crotalidae Polyvalent Immune Fab - Bryan Corbett; Jenna Otter; Clifford P. Masom; Richard F. Clark (Journal of Medical Toxicology, 2021)

A framework for high-resolution phenotyping of candidate male infertility mutants: from human to mouse - Brendan J. Houston; Donald F. Conrad; Moira K. O’Bryan (Human Genetics, 2021)

A multi-century, tree-ring-derived perspective of the North Cascades (USA) 2014–2016 snow drought - Grant L. Harley; R. Stockton Maxwell; Bryan A. Black; Matthew F. Bekker (Climatic Change, 2020)

Population genomic diversity and structure at the discontinuous southern range of the Great Gray Owl in North America - Beth Mendelsohn; Bryan Bedrosian; Sierra M. Love Stowell; Roderick B. Gagne; Melanie E. F. LaCava; Braden L. Godwin; Joshua M. Hull; Holly B. Ernest (Conservation Genetics, 2020)

COVID-19: Therapeutics and Their Toxicities - Michael A. Chary; Alexander F. Barbuto; Sudeh Izadmehr; Bryan D. Hayes; Michele M. Burns (Journal of Medical Toxicology, 2020)

Good Practices for Species Distribution Modeling of Deep-Sea Corals and Sponges for Resource Management: Data Collection, Analysis, Validation, and Communication - Arliss J. Winship; James T. Thorson; M. Elizabeth Clarke; Heather M. Coleman; Bryan Costa; Samuel E. Georgian; David Gillett; Arnaud Grüss; Mark J. Henderson; Thomas F. Hourigan; David D. Huff; Nissa Kreidler; et al. (Frontiers in Marine Science, 2020)

Spectral differences in the underwater light regime caused by sediment types in New Zealand estuaries: implications for seagrass photosynthesis - Mariana Coppede Cussioli; Dorothea Seeger; Daniel R. Pratt; Karin R. Bryan; Kai Bischof; Willem P. de Lange; Janet F. Bornman; Conrad A. Pilditch (Geo-Marine Letters, 2020)

A meta‐analysis reveals temperature, dose, life stage, and taxonomy influence host susceptibility to a fungal parasite - Erin L. Sauer; Jeremy M. Cohen; Marc J. Lajeunesse; Taegan A. McMahon; David J. Civitello; Sarah A. Knutie; Karena Nguyen; Elizabeth A. Roznik; Brittany F. Sears; Scott Bessler; Bryan K. Delius; Neal Halstead; et al. (Ecology, 2020)
Complex ecological relationships, such as host–parasite interactions, are often modeled with laboratory experiments. However, some experimental laboratory conditions, such as temperature or infection dose, are regularly chosen based on convenience or convention, and it is unclear how these decisions systematically affect experimental outcomes. Here, we conducted a meta‐analysis of 58 laboratory studies that exposed amphibians to the pathogenic fungus Batrachochytrium dendrobatidis (Bd) to understand better how laboratory temperature, host life stage, infection dose, and host species affect host mortality. We found that host mortality was driven by thermal mismatches: hosts native to cooler environments experienced greater Bd‐induced mortality at relatively warm experimental temperatures and vice versa. We also found that Bd dose positively predicted Bd‐induced host mortality and that the superfamilies Bufonoidea and Hyloidea were especially susceptible to Bd. Finally, the effect of Bd on host mortality varied across host life stages, with larval amphibians experiencing lower risk of Bd‐induced mortality than adults or metamorphs. Metamorphs were especially susceptible and experienced mortality when inoculated with much smaller Bd doses than the average dose used by researchers. Our results suggest that when designing experiments on species interactions, researchers should carefully consider the experimental temperature, inoculum dose, and life stage, and taxonomy of the host species.

A novel GIS-based tool to reveal spatial trends in reaction norm: upland rice case study - Germano Martins F. Costa-Neto; Odilon P. Morais Júnior; Alexandre Bryan Heinemann; Adriano Pereira de Castro; João Batista Duarte (Euphytica, 2020)

Migrations and movements of Atlantic tarpon revealed by two decades of satellite tagging - Jiangang Luo; Jerald S. Ault; Bruce T. Ungar; Steven G. Smith; Michael F. Larkin; Thomas N. Davidson; David R. Bryan; Nicholas A. Farmer; Scott A. Holt; A. Scott Alford; Aaron J. Adams; Robert Humston; et al. (Fish and Fisheries, 2020)
Understanding large‐scale migratory behaviours, local movement patterns and population connectivity are critical to determining the natural processes and anthropogenic stressors that influence population dynamics and for developing effective conservation plans. Atlantic tarpon occur over a broad geographic range in the Atlantic Ocean where they support valuable subsistence, commercial and recreational fisheries. From 2001 through 2018, we deployed 292 satellite telemetry tags on Atlantic tarpon in coastal waters off three continents to document: (a) seasonal migrations and regional population connectivity; (b) freshwater and estuarine habitat utilization; (c) spawning locations; and (d) shark predation across the south‐eastern United States, Gulf of Mexico and northern Caribbean Sea. These results showed that some mature tarpon make long seasonal migrations over thousands of kilometres crossing state and national jurisdictional borders. Others showed more local movements and habitat use. The tag data also revealed potential spawning locations consistent with those inferred in other studies from observations of early life stage tarpon leptocephalus larvae. Our analyses indicated that shark predation mortality on released tarpon is higher than previously estimated, especially at ocean passes, river mouths and inlets to bays. To date, there has been no formal stock assessment of Atlantic tarpon, and regional fishery management plans do not exist. Our findings will provide critical input to these important efforts and assist the multinational community in the development of a stock‐wide management information system to support informed decision‐making for sustaining Atlantic tarpon fisheries.

Slocum Gliders Provide Accurate Near Real-Time Estimates of Baleen Whale Presence From Human-Reviewed Passive Acoustic Detection Information - Mark F. Baumgartner; Julianne Bonnell; Peter J. Corkeron; Sofie M. Van Parijs; Cara Hotchkin; Ben A. Hodges; Jacqueline Bort Thornton; Bryan L. Mensi; Scott M. Bruner (Frontiers in Marine Science, 2020)

Changes in Arctic moisture transport over the North Pacific associated with sea ice loss - Marie C. McGraw; Cory F. Baggett; Chengji Liu; Bryan D. Mundhenk (Climate Dynamics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Multiyear monitoring of survival following mitigation‐driven translocation of a long‐lived threatened reptile - Brett G. Dickson; Rick D. Scherer; Amanda M. Kissel; Bryan P. Wallace; Kathryn M. Langin; Miranda E. Gray; Amanda F. Scheib; Bruce Weise (Conservation Biology, 2019)
Translocation is used by managers to mitigate the negative impacts of development on species. Moving individuals to a new location is challenging, and many translocation attempts have failed. Robust, posttranslocation monitoring is therefore important for evaluating effects of translocation on target species. We evaluated the efficacy of a translocation designed to mitigate the effects of a utility‐scale solar energy project on the U.S. federally listed Mojave desert tortoise ( Gopherus agassizii ). The species is a long‐lived reptile threatened by a variety of factors, including habitat loss due to renewable energy development in the Mojave Desert and portions of the Colorado Desert in southern California (southwestern United States). We translocated 58 individual tortoises away from the project's construction site and intensively monitored them over 5 years (2012–2017). We monitored these individuals and tortoises located in the translocation release area (resident tortoises; n = 112) and control tortoises ( n = 149) in a nearby location. We used our tortoise encounter data and known‐fate survival models to estimate annual and cumulative survival. Translocated tortoises in each of 2 size classes (120–160 mm, >160 mm) did not survive at lower rates than resident and control tortoises over the study period. For models with different sets of biotic and abiotic covariates, annual and cumulative estimates of survival were always >0.87 and >0.56, respectively. Larger tortoises tended to have higher survival, but translocated tortoises were not differentially affected by the covariates used to model variation in survival. Based on these findings, our translocation design and study protocols could inform other translocation projects for desert species. Our case study highlights the benefits of combining rigorous scientific monitoring with well‐designed, mitigation‐driven management actions to reduce the negative effects of development on species of conservation concern.

A comparison of organic fungicides: alternatives for reducing scab on pecan - Clive H. Bock; Michael W. Hotchkiss; David I. Shapiro-Ilan; Jason H. Brock; Timothy B. Brenneman; Bryan Wilkins; Daniel E. Wells; Lenny Wells; Russ F. Mizell (Organic Agriculture, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Locating and eliminating feral swine from a large area of fragmented mixed forest and agriculture habitats in north-central USA - Richard M. Engeman; Bradley E. Wilson; Scott F. Beckerman; Justin W. Fischer; Doug Dufford; James Bryan Cobban (Environmental Science and Pollution Research, 2019)

The development and use of a spatially explicit model for river otters to evaluate environmental hazards: a case study on the Department of Energy’s Savannah River Site - Emily B. McCallen; Karen F. Gaines; James M. Novak; Leslie E. Ruyle; Warren L. Stephens; A. Lawrence Bryan; Susan A. Blas; Thomas L. Serfass (Environmental Monitoring and Assessment, 2018)

Idiosyncratic responses to climate‐driven forest fragmentation and marine incursions in reed frogs from Central Africa and the Gulf of Guinea Islands - Rayna C. Bell; Juan L. Parra; Gabriel Badjedjea; Michael F. Barej; David C. Blackburn; Marius Burger; Alan Channing; Jonas Maximilian Dehling; Eli Greenbaum; Václav Gvoždík; Jos Kielgast; Chifundera Kusamba; et al. (Molecular Ecology, 2017)
Organismal traits interact with environmental variation to mediate how species respond to shared landscapes. Thus, differences in traits related to dispersal ability or physiological tolerance may result in phylogeographic discordance among co‐distributed taxa, even when they are responding to common barriers. We quantified climatic suitability and stability, and phylogeographic divergence within three reed frog species complexes across the Guineo‐Congolian forests and Gulf of Guinea archipelago of Central Africa to investigate how they responded to a shared climatic and geological history. Our species‐specific estimates of climatic suitability through time are consistent with temporal and spatial heterogeneity in diversification among the species complexes, indicating that differences in ecological breadth may partly explain these idiosyncratic patterns. Likewise, we demonstrated that fluctuating sea levels periodically exposed a land bridge connecting Bioko Island with the mainland Guineo‐Congolian forest and that habitats across the exposed land bridge likely enabled dispersal in some species, but not in others. We did not find evidence that rivers are biogeographic barriers across any of the species complexes. Despite marked differences in the geographic extent of stable climates and temporal estimates of divergence among the species complexes, we recovered a shared pattern of intermittent climatic suitability with recent population connectivity and demographic expansion across the Congo Basin. This pattern supports the hypothesis that genetic exchange across the Congo Basin during humid periods, followed by vicariance during arid periods, has shaped regional diversity. Finally, we identified many distinct lineages among our focal taxa, some of which may reflect incipient or unrecognized species.

Impacts of a bivalve mass mortality event on an estuarine food web and bivalve grazing pressure - Hannah F. E. Jones; Conrad A. Pilditch; David P. Hamilton; Karin R. Bryan (New Zealand Journal of Marine and Freshwater Research, 2017)
Declines in bivalve populations have been quite common worldwide, often associated with coastal development, pollution and climate change. In addition to the impacts of these chronic stressors, occasional mass mortality events may have severe consequences on ecosystem services and biodiversity. In this study, we examined the impact of a mass mortality event of the clam ( Austrovenus stutchburyi ) on an estuarine food web and the grazing pressure exerted by the bivalve population. In February 2009, c. 60% of the clam population died in Whangateau Harbour, New Zealand. Population clearance rate calculations suggest that the clam population do not exert significant top‐down control on phytoplankton biomass in the estuary, and thus the impact of the mortality event on bivalve grazing pressure was less severe than the reduction in abundance would suggest. A trophic model shows that phytoplankton play a limited role in the estuary food web, which is instead dominated by microphytobenthos and clams. This study highlights the importance of microphytobenthos in shallow estuaries, and the application of the trophic model is a useful tool that can identify key components of the ecosystem and could help inform monitoring programmes.

The complex relationship between personal sense of connection to animals and self‐reported proenvironmental behaviors by zoo visitors - Alejandro Grajal; Jerry F. Luebke; Lisa‐Anne DeGregoria Kelly; Jennifer Matiasek; Susan Clayton; Bryan T. Karazsia; Carol D. Saunders; Susan R. Goldman; Michael E. Mann; Ricardo Stanoss (Conservation Biology, 2017)
The global biodiversity crisis requires an engaged citizenry that provides collective support for public policies and recognizes the consequences of personal consumption decisions. Understanding the factors that affect personal engagement in proenvironmental behaviors is essential for the development of actionable conservation solutions. Zoos and aquariums may be some of the only places where many people can explore their relations with wild animals and proenvironmental behaviors. Using a moderated‐mediation analysis of a survey of U.S. zoo and aquarium visitors ( n = 3588), we explored the relationship between the sense of connection to animals and self‐reported engagement in proenvironmental behaviors related to climate change and how this relationship is affected by certainty that climate change is happening, level of concern about climate change, and perceptions of effectiveness in personally addressing climate change. We found a significant, directional relationship between sense of connection to animals and self‐reported proenvironmental behaviors. Political inclination within the conservative to liberal spectrum did not affect the relationship. We conclude that a personal sense of connection to animals may provide a foundation for educational and communication strategies to enhance involvement in proenvironmental actions.

Incorporating climate change into ecosystem service assessments and decisions: a review - Rebecca K. Runting; Brett A. Bryan; Laura E. Dee; Fleur J. F. Maseyk; Lisa Mandle; Perrine Hamel; Kerrie A. Wilson; Kathleen Yetka; Hugh P. Possingham; Jonathan R. Rhodes (Global Change Biology, 2017)
Climate change is having a significant impact on ecosystem services and is likely to become increasingly important as this phenomenon intensifies. Future impacts can be difficult to assess as they often involve long timescales, dynamic systems with high uncertainties, and are typically confounded by other drivers of change. Despite a growing literature on climate change impacts on ecosystem services, no quantitative syntheses exist. Hence, we lack an overarching understanding of the impacts of climate change, how they are being assessed, and the extent to which other drivers, uncertainties, and decision making are incorporated. To address this, we systematically reviewed the peer‐reviewed literature that assesses climate change impacts on ecosystem services at subglobal scales. We found that the impact of climate change on most types of services was predominantly negative (59% negative, 24% mixed, 4% neutral, 13% positive), but varied across services, drivers, and assessment methods. Although uncertainty was usually incorporated, there were substantial gaps in the sources of uncertainty included, along with the methods used to incorporate them. We found that relatively few studies integrated decision making, and even fewer studies aimed to identify solutions that were robust to uncertainty. For management or policy to ensure the delivery of ecosystem services, integrated approaches that incorporate multiple drivers of change and account for multiple sources of uncertainty are needed. This is undoubtedly a challenging task, but ignoring these complexities can result in misleading assessments of the impacts of climate change, suboptimal management outcomes, and the inefficient allocation of resources for climate adaptation.

Risk Factors for Cryptococcal Meningitis: A Single United States Center Experience - Andrés F. Henao-Martínez; Lilyana Gross; Bryan Mcnair; Bruce McCollister; Kristen DeSanto; Jose G. Montoya; Leland Shapiro; J. David Beckham (Mycopathologia, 2016)

Coordination and cross-sectoral integration in REDD+: experiences from seven countries - Kaisa Korhonen-Kurki; Maria Brockhaus; Bryan Bushley; Andrea Babon; Maria F Gebara; Felicien Kengoum; Thuy Thu Pham; Salla Rantala; Moira Moeliono; Bimo Dwisatrio; Cynthia Maharani (Climate and Development, 2016)

Recurrent connections between Amazon and Atlantic forests shaped diversity in Caatinga four‐eyed frogs - Maria Tereza C. Thomé; Fernando Sequeira; Francisco Brusquetti; Bryan Carstens; Célio F. B. Haddad; Miguel Trefaut Rodrigues; João Alexandrino (Journal of Biogeography, 2016)
Aim The Caatinga is a widespread but poorly known biome in South America. Its historical stability is controversial and different types of evidence provide support to contrasting hypotheses. We investigate how past biome dynamics may have caused diversification in the endemic four‐eyed frog genus Pleurodema . Location Caatinga biome. Methods We sampled 353 individuals of Pleurodema alium and Pleurodema diplolister from 60 localities and genotyped them at 12 ( P. alium ) or 20 ( P. diplolister ) microsatellite loci. We sequenced a mitochondrial fragment for a subset (199) of the samples. After exploratory analyses to infer genetic structure between and within species, we designed seven biogeographical scenarios based on the literature on species distributions, palaeomodels and geological palaeoindicators. We tested these hypotheses by calculating the posterior probability of models using multilocus approximate Bayesian computation ( ABC ). Results Both markers recovered well‐defined interspecific limits with restricted introgression, but population structure within P. diplolister is subtle and affected by isolation by distance. Model selection using ABC supported two scenarios of diversification that included recent demographic growth. Genetic breaks at intra‐ and interspecific levels were geographically coincident, and correlated with past forest invasions reported in the literature. Main conclusions Our data support the idea that past expansions of the Amazon and Atlantic forests over the current Caatinga distribution shaped the genetic structure in endemic four‐eyed frogs at more than one level by promoting intermittent vicariance. Additional support comes from the distribution patterns of forest and C aatinga taxa. Variation among groups suggests differential organismal responses to past habitat shifts, probably mediated by specific natural‐history traits. This paper provides the first direct evidence that taxa endemic to the C aatinga were affected by past forest interactions.

Rock geochemistry induces stress and starvation responses in the bacterial proteome - Casey C. Bryce; Thierry Le Bihan; Sarah F. Martin; Jesse P. Harrison; Timothy Bush; Bryan Spears; Alanna Moore; Natalie Leys; Bo Byloos; Charles S. Cockell (Environmental Microbiology, 2016)
Summary Interactions between microorganisms and rocks play an important role in Earth system processes. However, little is known about the molecular capabilities microorganisms require to live in rocky environments. Using a quantitative label‐free proteomics approach, we show that a model bacterium ( C upriavidus metallidurans CH 34) can use volcanic rock to satisfy some elemental requirements, resulting in increased rates of cell division in both magnesium‐ and iron‐limited media. However, the rocks also introduced multiple new stresses via chemical changes associated with pH , elemental leaching and surface adsorption of nutrients that were reflected in the proteome. For example, the loss of bioavailable phosphorus was observed and resulted in the upregulation of diverse phosphate limitation proteins, which facilitate increase phosphate uptake and scavenging within the cell. Our results revealed that despite the provision of essential elements, rock chemistry drives complex metabolic reorganization within rock‐dwelling organisms, requiring tight regulation of cellular processes at the protein level. This study advances our ability to identify key microbial responses that enable life to persist in rock environments.

Transport and connectivity modeling of larval permit from an observed spawning aggregation in the Dry Tortugas, Florida - David R. Bryan; Jiangang Luo; Jerald S. Ault; David B. McClellan; Steven G. Smith; Derke Snodgrass; Michael F. Larkin (Environmental Biology of Fishes, 2015)

A paper-based scaffold for enhanced osteogenic differentiation of equine adipose-derived stem cells - Gayle F. Petersen; Bryan J. Hilbert; Gareth D. Trope; Wouter H. J. Kalle; Padraig M. Strappe (Biotechnology Letters, 2015)

Effects of climate change on the delivery of soil‐mediated ecosystem services within the primary sector in temperate ecosystems: a review and New Zealand case study - Kate H. Orwin; Bryan A. Stevenson; Simeon J. Smaill; Miko U. F. Kirschbaum; Ian A. Dickie; Brent E. Clothier; Loretta G. Garrett; Tony J. van der Weerden; Michael H. Beare; Denis Curtin; Cecile A. M. de Klein; Michael B. Dodd; et al. (Global Change Biology, 2015)
Future human well‐being under climate change depends on the ongoing delivery of food, fibre and wood from the land‐based primary sector. The ability to deliver these provisioning services depends on soil‐based ecosystem services (e.g. carbon, nutrient and water cycling and storage), yet we lack an in‐depth understanding of the likely response of soil‐based ecosystem services to climate change. We review the current knowledge on this topic for temperate ecosystems, focusing on mechanisms that are likely to underpin differences in climate change responses between four primary sector systems: cropping, intensive grazing, extensive grazing and plantation forestry. We then illustrate how our findings can be applied to assess service delivery under climate change in a specific region, using New Zealand as an example system. Differences in the climate change responses of carbon and nutrient‐related services between systems will largely be driven by whether they are reliant on externally added or internally cycled nutrients, the extent to which plant communities could influence responses, and variation in vulnerability to erosion. The ability of soils to regulate water under climate change will mostly be driven by changes in rainfall, but can be influenced by different primary sector systems' vulnerability to soil water repellency and differences in evapotranspiration rates. These changes in regulating services resulted in different potentials for increased biomass production across systems, with intensively managed systems being the most likely to benefit from climate change. Quantitative prediction of net effects of climate change on soil ecosystem services remains a challenge, in part due to knowledge gaps, but also due to the complex interactions between different aspects of climate change. Despite this challenge, it is critical to gain the information required to make such predictions as robust as possible given the fundamental role of soils in supporting human well‐being.

Visualization of coral host–pathogen interactions using a stable GFP-labeled Vibrio coralliilyticus strain - F. Joseph Pollock; Cory J. Krediet; Melissa Garren; Roman Stocker; Karina Winn; Bryan Wilson; Carla Huete-Stauffer; Bette L. Willis; David G. Bourne (Coral Reefs, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

The evolution of phylogeographic data sets - Ryan C. Garrick; Isabel A. S. Bonatelli; Chaz Hyseni; Ariadna Morales; Tara A. Pelletier; Manolo F. Perez; Edwin Rice; Jordan D. Satler; Rebecca E. Symula; Maria Tereza C. Thomé; Bryan C. Carstens (Molecular Ecology, 2015)
Empirical phylogeographic studies have progressively sampled greater numbers of loci over time, in part motivated by theoretical papers showing that estimates of key demographic parameters improve as the number of loci increases. Recently, next‐generation sequencing has been applied to questions about organismal history, with the promise of revolutionizing the field. However, no systematic assessment of how phylogeographic data sets have changed over time with respect to overall size and information content has been performed. Here, we quantify the changing nature of these genetic data sets over the past 20 years, focusing on papers published in Molecular Ecology . We found that the number of independent loci, the total number of alleles sampled and the total number of single nucleotide polymorphisms ( SNP s) per data set has improved over time, with particularly dramatic increases within the past 5 years. Interestingly, uniparentally inherited organellar markers (e.g. animal mitochondrial and plant chloroplast DNA ) continue to represent an important component of phylogeographic data. Single‐species studies (cf. comparative studies) that focus on vertebrates (particularly fish and to some extent, birds) represent the gold standard of phylogeographic data collection. Based on the current trajectory seen in our survey data, forecast modelling indicates that the median number of SNP s per data set for studies published by the end of the year 2016 may approach ~20 000. This survey provides baseline information for understanding the evolution of phylogeographic data sets and underscores the fact that development of analytical methods for handling very large genetic data sets will be critical for facilitating growth of the field.

Learning from the past to predict the future: an historical analysis of grass invasions in northern Australia - Rieks D. van Klinken; F. Dane Panetta; Shaun Coutts; Bryan K. Simon (Biological Invasions, 2015)

Historical trends of mercury and spheroidal carbonaceous particle deposition in sub-alpine lakes in the Great Basin, United States - Scott A. Reinemann; David F. Porinchu; Mae Sexauer Gustin; Bryan G. Mark (Journal of Paleolimnology, 2014)

Validation of PyMBMS as a High-throughput Screen for Lignin Abundance in Lignocellulosic Biomass of Grasses - Bryan W. Penning; Robert W. Sykes; Nicholas C. Babcock; Christopher K. Dugard; John F. Klimek; David Gamblin; Mark Davis; Timothy R. Filley; Nathan S. Mosier; Clifford F. Weil; Maureen C. McCann; Nicholas C. Carpita (BioEnergy Research, 2014)

Effect of selection and sequencing of representative wave conditions on process-based predictions of equilibrium embayed beach morphology - Christopher J. Daly; Karin R. Bryan; Mauricio R. Gonzalez; Antonio H. F. Klein; Christian Winter (Ocean Dynamics, 2014)

Climate, physiological tolerance and sex‐biased dispersal shape genetic structure of N eotropical orchid bees - Margarita M. López‐Uribe; Kelly R. Zamudio; Carolina F. Cardoso; Bryan N. Danforth (Molecular Ecology, 2014)
Understanding the impact of past climatic events on the demographic history of extant species is critical for predicting species' responses to future climate change. Palaeoclimatic instability is a major mechanism of lineage diversification in taxa with low dispersal and small geographical ranges in tropical ecosystems. However, the impact of these climatic events remains questionable for the diversification of species with high levels of gene flow and large geographical distributions. In this study, we investigate the impact of P leistocene climate change on three N eotropical orchid bee species ( E ulaema bombiformis , E . meriana and E . cingulata ) with transcontinental distributions and different physiological tolerances. We first generated ecological niche models to identify species‐specific climatically stable areas during P leistocene climatic oscillations. Using a combination of mitochondrial and nuclear markers, we inferred calibrated phylogenies and estimated historical demographic parameters to reconstruct the phylogeographical history of each species. Our results indicate species with narrower physiological tolerance experienced less suitable habitat during glaciations and currently exhibit strong population structure in the mitochondrial genome. However, nuclear markers with low and high mutation rates show lack of association with geography. These results combined with lower migration rate estimates from the mitochondrial than the nuclear genome suggest male‐biased dispersal. We conclude that despite large effective population sizes and capacity for long‐distance dispersal, climatic instability is an important mechanism of maternal lineage diversification in orchid bees. Thus, these N eotropical pollinators are susceptible to disruption of genetic connectivity in the event of large‐scale climatic changes.

Trophic dynamics of U, Ni, Hg and other contaminants of potential concern on the Department of Energy’s Savannah River Site - Paul G. Edwards; Karen F. Gaines; A. Lawrence Bryan; James M. Novak; Susan A. Blas (Environmental Monitoring and Assessment, 2014)

2-epi-5-epi-Valiolone synthase activity is essential for maintaining phycobilisome composition in the cyanobacterium Anabaena variabilis ATCC 29413 when grown in the presence of a carbon source - Edward Spence; Samantha J. Bryan; Mohamed Lisfi; John Cullum; Walter C. Dunlap; J. Malcolm Shick; Conrad W. Mullineaux; Paul F. Long (Photosynthesis Research, 2013)

Molecular Phylogeny and Evolution of the Proteins Encoded by Coleoid (Cuttlefish, Octopus, and Squid) Posterior Venom Glands - Tim Ruder; Kartik Sunagar; Eivind A. B. Undheim; Syed A. Ali; Tak-Cheung Wai; Dolyce H. W. Low; Timothy N. W. Jackson; Glenn F. King; Agostinho Antunes; Bryan G. Fry (Journal of Molecular Evolution, 2013)

Influence of human immune cells on cancer: studies at the University of Colorado - Tullia C. Bruno; Jena D. French; Kimberly R. Jordan; Oscar Ramirez; Trisha R. Sippel; Virginia F. Borges; Bryan R. Haugen; Martin D. McCarter; Allen Waziri; Jill E. Slansky (Immunologic Research, 2013)

Identification versus counting protocols as sources of uncertainty in diatom-based ecological status assessments - Maria Kahlert; Martyn Kelly; Raino-Lars Albert; Salomé F. P. Almeida; Tomáš Bešta; Saúl Blanco; Michel Coste; Luc Denys; Luc Ector; Markéta Fránková; Daša Hlúbiková; Plamen Ivanov; et al. (Hydrobiologia, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Toward Developing a Universal Treatment for Fungal Disease Using Radioimmunotherapy Targeting Common Fungal Antigens - R. A. Bryan; A. J. Guimaraes; S. Hopcraft; Z. Jiang; K. Bonilla; A. Morgenstern; F. Bruchertseifer; M. Del Poeta; A. Torosantucci; A. Cassone; J. D. Nosanchuk; A. Casadevall; et al. (Mycopathologia, 2012)

Biodiesel from Corn Distillers Dried Grains with Solubles: Preparation, Evaluation, and Properties - Bryan R. Moser; Steven F. Vaughn (BioEnergy Research, 2012)

The missing wetlands: using local ecological knowledge to find cryptic ecosystems - Amber L. Pitt; Robert F. Baldwin; Donald J. Lipscomb; Bryan L. Brown; Joanna E. Hawley; Cora M. Allard-Keese; Paul B. Leonard (Biodiversity and Conservation, 2012)

Islands at bay: rising seas, eroding islands, and waterbird habitat loss in Chesapeake Bay (USA) - R. Michael Erwin; David F. Brinker; Bryan D. Watts; Gary R. Costanzo; David D. Morton (Journal of Coastal Conservation, 2011)

Critical evaluation of solid waste sample processing for DNA-based microbial community analysis - Bryan F. Staley; Pascal E. Saikaly; Francis L. de los Reyes; Morton A. Barlaz (Biodegradation, 2011)

Systems Analysis of Small Signaling Modules Relevant to Eight Human Diseases - Kelly F. Benedict; Feilim Mac Gabhann; Robert K. Amanfu; Arvind K. Chavali; Erwin P. Gianchandani; Lydia S. Glaw; Matthew A. Oberhardt; Bryan C. Thorne; Jason H. Yang; Jason A. Papin; Shayn M. Peirce; Jeffrey J. Saucerman; et al. (Annals of Biomedical Engineering, 2011)

Do salmon lice, Lepeophtheirus salmonis , have a role in the epidemiology of amoebic gill disease caused by Neoparamoeba perurans ? - B F Nowak; J Bryan; S R M Jones (Journal of Fish Diseases, 2010)

Role of kappa-opioid receptors in the effects of salvinorin A and ketamine on attention in rats - Christina L. Nemeth; Tracie A. Paine; Joseph E. Rittiner; Cécile Béguin; F. Ivy Carroll; Bryan L. Roth; Bruce M. Cohen; William A. Carlezon (Psychopharmacology, 2010)

Reproductive factors and risk of contralateral breast cancer by BRCA1 and BRCA2 mutation status: results from the WECARE study - Jenny N. Poynter; Bryan Langholz; Joan Largent; Lene Mellemkjær; Leslie Bernstein; Kathleen E. Malone; Charles F. Lynch; Åke Borg; Patrick Concannon; Sharon N. Teraoka; Shanyan Xue; Anh T. Diep; et al. (Cancer Causes & Control, 2010)

Sequencing the Potato Genome: Outline and First Results to Come from the Elucidation of the Sequence of the World’s Third Most Important Food Crop - Richard G. F. Visser; Christian W. B. Bachem; Jan M. de Boer; Glenn J. Bryan; Swarup K. Chakrabati; Sergio Feingold; Robert Gromadka; Roeland C. H. J. van Ham; Sanwen Huang; Jeanne M. E. Jacobs; Boris Kuznetsov; Paulo E. de Melo; et al. (American Journal of Potato Research, 2009)

Estimating habitat selection when GPS fix success is less than 100% - Ryan M. Nielson; Bryan F. J. Manly; Lyman L. McDonald; Hall Sawyer; Trent L. McDonald (Ecology, 2009)
Inferences about habitat selection by animals derived from sequences of relocations obtained with global positioning system (GPS) collars can be influenced by GPS fix success. Environmental factors such as dense canopy cover or rugged terrain can reduce GPS fix success, making subsequent modeling problematic if fix success depends on the selected habitat. Ignoring failed fix attempts may affect estimates of model coefficients and lead to incorrect conclusions about habitat selection. Here, we present a habitat selection model that accounts for missing locations due to habitat‐induced data losses, called a resource selection function (RSF) for GPS fix success. The model's formulation is similar to adjusting estimates of probability of occupancy when detection is less than 100% in patch occupancy sampling. We demonstrate use of the model with GPS data collected from an adult female mule deer ( Odocoileus hemionus ) and discuss how to analyze data from multiple animals. In the simulations presented, our habitat selection model was generally unbiased for GPS data sets missing up to 50% of the locations.

Defining Optimal Freshwater Flow for Oyster Production: Effects of Freshet Rate and Magnitude of Change and Duration on Eastern Oysters and Perkinsus marinus Infection - Megan K. La Peyre; Bryan Gossman; Jerome F. La Peyre (Estuaries and Coasts, 2009)

Genes driving potato tuber initiation and growth: identification based on transcriptional changes using the POCI array - Bjorn Kloosterman; David De Koeyer; Rebecca Griffiths; Barry Flinn; Burkhard Steuernagel; Uwe Scholz; Sophia Sonnewald; Uwe Sonnewald; Glenn J. Bryan; Salomé Prat; Zsófia Bánfalvi; John P. Hammond; et al. (Functional & Integrative Genomics, 2008)

Genetic analysis of opaque2 modifier loci in quality protein maize - David R. Holding; Brenda G. Hunter; Taijoon Chung; Bryan C. Gibbon; Clark F. Ford; Arvind K. Bharti; Joachim Messing; Bruce R. Hamaker; Brian A. Larkins (Theoretical and Applied Genetics, 2008)

Resilience of North Sea phytoplankton spring bloom dynamics: An analysis of long‐term data at Helgoland Roads - Karen Helen Wiltshire; Arne Michael Malzahn; Kai Wirtz; Wulf Greve; Silvia Janisch; Peter Mangelsdorf; Bryan F. J. Manly; Maarten Boersma (Limnology and Oceanography, 2008)
Analyzing one of the most extensive long‐term data series in the North Sea, the Helgoland Roads time series, we investigated the changes in the factors that potentially drive phytoplankton bloom dynamics in the German Bight. We compared the changes in these factors with the changes in the spring bloom phenology. We combined zooplankton, nutrient, weather, and phytoplankton data to analyze whether there has been a shift in trophic interactions in the North Sea affecting the spring bloom timing. The potential influence of temperature, with a mean increase of 1.5°C, was investigated. We showed that the German Bight around Helgoland is a highly dynamic system and has undergone considerable change in the last 30 yr. Nutrient levels, temperature, underwater light climate and wind speed have all changed. However, the spring bloom dynamics have hardly changed at all. We showed that the spring bloom tends to come later in warmer years but that this is not directly correlated with the overall warming trend. The known regime shift of the late 1980s is clearly visible in our data in terms of average phytoplankton winter densities and average cell size, but even so the start of the spring bloom has not changed.

Inhibition of phosphorus sorption to goethite, gibbsite, and kaolin by fresh and decomposed organic matter - James F. Hunt; Tsutomu Ohno; Zhongqi He; C. Wayne Honeycutt; D. Bryan Dail (Biology and Fertility of Soils, 2007)

Construction of a drainage channel at Inner Deep Bay, Hong Kong: mitigating ecological and landscape impact through an environmentally friendly design - Patrick C. C. Lai; W. H. Lee; Bryan S. F. Wong (Landscape and Ecological Engineering, 2007)

Local adaptation of immunity against a trematode parasite in marine amphipod populations - Kim Bryan-Walker; Tommy L. F. Leung; Robert Poulin (Marine Biology, 2007)

Recent hybrid origin of three rare Chinese turtles - Bryan L. Stuart; James F. Parham (Conservation Genetics, 2006)

Forskolin, an inducer of cAMP, up-regulates acetylcholinesterase expression and protects against organophosphate exposure in neuro 2A cells - Bryan F. Curtin; Nabaneeta Pal; Richard K. Gordon; Madhusoodana P. Nambiar (Molecular and Cellular Biochemistry, 2006)

The generation of diversity in systems of patches and ranked dominance - Jorge A. Navarro Alberto; Bryan F. J. Manly (Journal of Biogeography, 2006)
Aim Mac Nally and Lake proposed a statistic ( η ) for determining whether the diversity in archipelagos is better generated by several small patches (SS‐dominance) or by a few large patches (SL‐dominance). The η statistic improves the study of the generation of diversity in systems of patches, but the dependence of η on a particular species–area relationship may reduce its effectiveness. In this paper we show that η may be affected by the criterion used to distinguish between large and small patches. We propose alternative measures (ranked m ‐dominance indices) for the detection of SS/SL dominance, which separate the effects of each class of patch size on the generation of diversity. Location We use previously published species lists from three archipelagos: lizard species on 25 islands in the Gulf of California; non‐introduced species of reptiles of the Canary Islands (order Squamata); and finch species from 19 islands of the West Indies. We also use one artificial data set. Methods Presence–absence data and the rank order of patch areas are used to define the m ‐dominance indices, interpreted as measures of preferential size of patches occupied by m species. A Monte Carlo procedure is implemented for testing the significance of the observed indices. Row and column totals in the simulated presence–absence matrices are kept fixed in order to maintain differences in species richness among sites and differences in occurrence frequencies among species, but the allocation of each occurrence to a specific ranked area is randomized. The analyses are exemplified with the three published data sets taken from the literature, and a hypothetical patch system neither SS‐ nor SL‐dominated. Results The new m ‐dominance indices identified correctly the hypothetical patch system, while η was positive, suggesting an incorrect SL‐dominant result. For the lizard data set, the standardized ranked m ‐dominance was significantly large for small m , confirming an SL‐dominated system. Islands of varying size in the Canary archipelago hosted restricted reptile species, but matrix sparseness seems to have caused the non‐significant results for the m ‐dominance indices in this case. The overall pattern of the West Indies system shows that medium‐large islands are dominant, but most Monte Carlo analyses were not significant, also possibly as a result of matrix sparseness. Main conclusions The m ‐dominance indices have the virtue of summarizing composition–area relationships, and including Monte Carlo procedures for testing whether patch size and the type of species distribution (species restricted to m patches, m = 1,…, s ) are random or not. When m is as low as 1 or 2, the m ‐dominance indices may typify the role of restricted species on the generation of diversity in the system of patches. The procedure developed here can be generalized to include other ordinal properties of patches, such as isolation or habitat heterogeneity.

Divalent metal-ion transporter DMT1 mediates both H+ -coupled Fe2+ transport and uncoupled fluxes - Bryan Mackenzie; M. L. Ujwal; Min-Hwang Chang; Michael F. Romero; Matthias A. Hediger (Pflügers Archiv - European Journal of Physiology, 2006)

Effects of Geldanamycin on Hatching and Juvenile Motility in Caenorhabditis elegans and Heterodera glycines - Andrea M. Skantar; Keli Agama; Susan L. F. Meyer; Lynn K. Carta; Bryan T. Vinyard (Journal of Chemical Ecology, 2005)

TRENDS IN ABUNDANCE AND CURRENT STATUS OF HARBOR SEALS IN OREGON: 1977–2003 - Robin F. Brown; Bryan E. Wright; Susan D. Riemer; Jeffrey Laake (Marine Mammal Science, 2005)

Reconstruction of glacier equilibrium‐line altitudes for the Last Glacial Maximum on the High Plain of Bogotá, Eastern Cordillera, Colombia: climatic and topographic implications - Bryan G. Mark; Karin F. Helmens (Journal of Quaternary Science, 2005)
The High Plain of Bogotá in the Andes of Colombia provides an exceptionally detailed record of glaciation. A two‐stage Last Glacial Maximum (LGM) is noted in Bogotá; the older stage (max) presents an opportunity to reconstruct individual valley glaciers and explore spatial patterns. Well‐mapped geomorphic features on topographic base maps permit the reconstruction of 23 palaeoglacier surfaces. Glacier extent varies across the region, with lower altitudes reached farther to the east. Equilibrium line altitudes (ELAs) are reconstructed using the area–altitude balance ratio (AABR) method, with BRs in three groups reflecting the W–E gradient in glacier extent and selected by minimising variation from group means. Average LGM ELA for all palaeoglaciers is 3488 m with a standard deviation of 182 m. The average lowering in ELA from LGM to modern of ca. 1300 m is best explained by a considerable drop in temperature. Significant intra‐regional variance in LGM ELA can be ascribed to topography and its influence on precipitation and/or glacier form, with lower headwall elevations being correlated to larger accumulation areas. Copyright © 2005 John Wiley & Sons, Ltd.

Erratum to: Functionally associated molecular genetic marker map construction in perennial ryegrass (Lolium perenne L.) - M. J. Faville; A. C. Vecchies; M. Schreiber; M. C. Drayton; L. J. Hughes; E. S. Jones; K. M. Guthridge; K. F. Smith; T. Sawbridge; G. C. Spangenberg; G. T. Bryan; J. W. Forster (Theoretical and Applied Genetics, 2005)

Functionally associated molecular genetic marker map construction in perennial ryegrass (Lolium perenne L.) - M. J. Faville; A. C. Vecchies; M. Schreiber; M. C. Drayton; L. J. Hughes; E. S. Jones; K. M. Guthridge; K. F. Smith; T. Sawbridge; G. C. Spangenberg; G. T. Bryan; J. W. Forster (Theoretical and Applied Genetics, 2004)

Using the bootstrap with two-phase adaptive stratified samples from multiple populations at multiple locations - Bryan F. J. Manly (Environmental and Ecological Statistics, 2004)

Two‐phase stratified random surveys on multiple populations at multiple locations - Bryan F. J. Manly; Jo‐Anne M. Akroyd; Kim A. R. Walshe (New Zealand Journal of Marine and Freshwater Research, 2002)
The two‐phase random stratified sampling design proposed by Francis (1984) was designed for situations where prior information is insufficient to ensure an efficient allocation of sampling effort to different strata. It involves taking a first‐phase sample, and then using the data from this to allocate a second‐phase sample which compensates for any shortcomings of the first‐phase sample. Here we generalise this method to situations where several species are sampled simultaneously, and at several locations. The method then uses the first‐phase sample results to decide how best to allocate a second‐phase sample to locations and strata. We provide the results of a simulation study based on model populations of shellfish which demonstrates the effectiveness of the method. We use a survey of cockles, pipis, and tuatuas on 11 Auckland Fisheries Management Area beaches as an example of its use.

Mammal extinctions on Australian islands: causes and conservation implications - Andrew A. Burbidge; Bryan F. J. Manly (Journal of Biogeography, 2002)
Aim Data on Australian landbridge islands were analysed to seek relationships between the extinction of mammals on islands and a number of variables related to the islands, the native mammal species that occur on them and the presence or absence of exotic mammalian predators. The data base included attributes of the mammals (mean adult body weight, diet and shelter habitat) and of the islands [area, rainfall, presence/absence of significant areas of rockpile habitat, presence/absence of European red fox Vulpes vulpes Linnaeus, 1758, feral cat Felis catus Linnaeus, 1758, and rats Rattus rattus (Linnaeus, 1758) and R. exulans (Peale, 1848)]. Methods Statistical analysis of the 388 cases where a Critical Weight Range (CWR) mammal is extant and the forty‐one cases where a CWR mammal is extinct was conducted using logistic regression to model the probability of extinction as a function of the island and mammal variables. Results Foxes and cats are correlated with CWR mammal extinctions, but cats are associated with extinctions particularly on more arid islands. Extinctions are more likely on islands with an absence of significant areas of rockpile habitat and where the native mammal is restricted to the ground's surface, and is relatively large. Conclusions An association between the presence of cats and native mammal extinctions has not previously been demonstrated for Australian islands. The introduction of exotic predators to Australian islands with native mammal species should be avoided and should any of these predators establish all means should be employed to eradicate them. For Australian continental islands the introduction of exotic predators, not habitat clearance, has been the major factor in extinctions.

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

Abnormal subcellular distribution of mature MUC2 and de novo MUC5AC mucins in adenomas of the rectum: Immunohistochemical detection using non-VNTR antibodies to MUC2 and MUC5AC peptide - Neil Myerscough; Paul A. Sylvester; Bryan F. Warren; Simon Biddolph; Paul Durdey; Michael G. Thomas; Ingemar Carlstedt; Anthony P. Corfield (Glycoconjugate Journal, 2001)

Physical mapping across an avirulence locus of Phytophthora infestans using a highly representative, large-insert bacterial artificial chromosome library - S. Whisson; T. Lee; G. Bryan; R. Waugh; F. Govers; P. Birch (Molecular Genetics and Genomics, 2001)

Mus and Peromyscus chromosome homology established by FISH with three mouse paint probes - Wallace D. Dawson; S. Robert Young; Zongren Wang; Linda W. Liu; Ira F. Greenbaum; Lisa M. Davis; Bryan K. Hall (Mammalian Genome, 1999)

Reduction of sialic acid O-acetylation in human colonic mucins in the adenoma-carcinoma sequence - Anthony P. Corfield; Neil Myerscough; Bryan F. Warren; Paul Durdey; Christos Paraskeva; Roland Schauer (Glycoconjugate Journal, 1999)

Assortative Mating in Two Pheromone Strains of the Cabbage Looper Moth, Trichoplusia ni - Junwei Zhu; Bonnie B. Chastain; Bryan G. Spohn; Kenneth F. Haynes (Journal of Insect Behavior, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Detection of harmful algal blooms using photopigments and absorption signatures: A case study of the Florida red tide dinoflagellate, Gymnodinium breve - David F. Millie; Oscar M. Schofield; Gary J. Kirkpatrick; Geir Johnsen; Patricia A. Tester; Bryan T. Vinyard (Limnology and Oceanography, 1997)
The utility of photopigments and absorption signatures to detect and enumerate the red tide dinoflagellate, Gymnodinium breve, was evaluated in laboratory cultures and in natural assemblages. The carotenoid, gyroxanthindiester, was an adequate biomarker for G. breve biomass; water‐column concentrations corresponded with cell standing crops and chlorophyll a concentrations during bloom events in Sarasota Bay, Florida. Unlike other carotenoids, the relative abundance of gyroxanthin‐diester did not change throughout a range of physiological states in culture and the gyroxanthin‐diester: chlorophyll a ratio exhibited little variability in a natural assemblage during bloom senescence. Stepwise discriminant analysis indicated that wavelengths indicative of in vivo absorption by accessory chlorophylls and carotenoids could correctly discern spectra of the fucoxanthin‐containing G. breve from spectra of peridinin‐containing dinoflagellates, a diatom, a haptophyte, and a prasinophyte. With the use of a similarity algorithm, the increasing contribution of G. breve was discerned in absorption spectra (and corresponding fourth‐derivative plots) for hypothetical mixed assemblages. However, the absorption properties of chlorophyll c ‐containing algae vary little among taxa and it is difficult to discern the contribution of accessory chlorophylls and carotenoids caused by cell packaging. Therefore, the use of absorption spectra alone may not identify the contribution of a chlorophyll c ‐containing taxon to the composite spectrum of a mixed assemblage. This difficulty in distinguishing among spectra can be minimized by using the similarity algorithm in conjunction with fourth‐derivative analysis.

Hoffmann half-frame external fixation rigidity and its relationship to universal joint slippage - F. L. I. Philip Drijber; J. Bryan Finlay (Annals of Biomedical Engineering, 1992)

Life members announced - Jay G. Garner; R. W. Chase; James E. Bryan; David Curwen; F. J. Cole (American Journal of Potato Research, 1985)